Laminin-511 and laminin-521-based matrices for efficient hepatic specification of human pluripotent stem cells. (October 2016) - Kanninen, Liisa K.; Harjumäki, Riina; Peltoniemi, Pasi; Bogacheva, Mariia S.; Salmi, Tuuli; Porola, Pauliina; Niklander, Johanna; Smutný, Tomáš; Urtti, Arto; Yliperttula, Marjo L.; Lou, Yan-Ru
Abstract: Human pluripotent stem cells (hPSCs) have gained a solid foothold in basic research and drug industry as they can be used in vitro to study human development and have potential to offer limitless supply of various somatic cell types needed in drug development. Although the hepatic differentiation of hPSCs has been extensively studied, only a little attention has been paid to the role of the extracellular matrix. In this study we used laminin-511, laminin-521, and fibronectin, found in human liver progenitor cells, as culture matrices for hPSC-derived definitive endoderm cells. We observed that laminin-511 and laminin-521 either alone or in combination support the hepatic specification and that fibronectin is not a vital matrix protein for the hPSC-derived definitive endoderm cells. The expression of the laminin-511/521-specific integrins increased during the definitive endoderm induction and hepatic specification. The hepatic cells differentiated on laminin matrices showed the upregulation of liver-specific markers both at mRNA and protein levels, secreted human albumin, stored glycogen, and exhibited cytochrome P450 enzyme activity and inducibility. Altogether, we found that laminin-511 and laminin-521 can be used as stage-specific matrices to guide the hepatic specification of hPSC-derived definitive endoderm cells.